The degree of possession of mental arithmetic skills by intermediate school girls in Abha city from the teachers’ point of view (The International Journal for Scientific Research, 2024)
The research aimed to determine the degree to which middle school students in the city of Abha possessed mental arithmetic skills from the teachers’ point of view. The research used a social survey approach, and the sample consisted of (94) female teachers. The research concluded that the degree to which middle school students possessed mental arithmetic skills was low with an average arithmetic ( 1.50) from the point of view of teachers in the city of Abha, where the arithmetic averages of the research sample’s responses ranged between (1.91 – 1.11), The research recommended the necessity of holding training courses to develop the skills of mathematics teachers to train female students to use mental arithmetic skills, the necessity of diversity among mathematics teachers in using modern teaching methods to teach mathematical concepts, and the necessity of preparing programs and applications to enhance mental arithmetic skills among middle school female students.
Keywords: Middle School Students; Mental Arithmetic; Mathematics; Teachers